PERANCANGAN VIRTUAL FRIEND MENGGUNAKAN ALGORITMA CASE-BASED REASONING BERBASIS APLIKASI DESKTOP - Bima Amei Prayansyah (Jurnal Mantik Penusa, 2016)
Technology has an important part in many area of people life. Almost every sector of human life is always associated with the technology. Currently, a lot of two-way technology has developed but the technology that developed in the computer is still limited in the type and feedback given. Feedback provided by the computer will give an added value to the user, in addition to the feedback given will provide convenienc e to the user in the use of the computer.To improve the quality of feedback that given by the computer required an additional application that allows computers to process user input. From the results of the input, the data will be processed to generate feedback in the form of sound that are sustainable. By implementing the Case-Based Reasoning in a system, the computer will provide feedback that are sustainable in accordance with what the user input. Analytical results obtained from the research is the feedback given by the computer in the form of sound that are sustainable give more interactive value to the user computer because by implementing the existing system into a computer can create a system that is friendly to the user.